Interaction and compatibility studies of efavirenz with pharmaceutical excipients - Cinira Fandaruff; Andrea Mariela Araya-Sibaja; Rafael Nicolay Pereira; Silvia Lucia Cuffini; Carlos Eduardo Maduro de Campos; Cristiane Rodrigues Drago Hoffmeister; Helvécio Vinícius Antunes Rocha; Marco Antônio Segatto Silva (Journal of Excipients and Food Chemicals, 2016)
Although excipients have traditionally been thought of as being inert, experience has shown that there can be interactions between excipients and drugs. Thus, knowledge of potential physical and chemical interactions can be very useful. The compatibility of efavirenz with the excipients: sodium lauryl sulfate, spray dried lactose, hydroxypropylcellulose, magnesium stearate, microcrystalline cellulose and croscarmellose sodium was studied. X-ray powder diffraction (XRPD), Fourier Transform Infrared Spectroscopy (FT-IR), Raman spectroscopy (RS) and Differential scanning calorimetry (DSC) were used as screening techniques. DSC curves of binary mixtures were quite different from the efavirenz raw material, suggesting a strong interaction, including possible chemical reactions between efavirenz and excipients at increased temperatures. However, FT-IR, XRPD and RS showed that no chemical reaction occurred between efavirenz and excipients at room temperature. Efavirenz can exist in more than one crystalline form, which may have implications for its behavior during production, and also for its in vivo performance. XRPD, DSC, Scanning Electron Microscopy (SEM) and Intrinsic Dissolution Rate (IDR) were used for the solid-state characterization of efavirenz and showed that the raw material used corresponded to Form I and maintained its crystal structure during the study. Intrinsic dissolution studies indicated that bioavailability problems may arise because of the poor solubility of efavirenz.